Reliability and characterisation of the 20-maximum trampoline jump test - Dyas, N.; Green, D.; Thomas, K.; Howatson, G. (Isokinetics and Exercise Science, 2021)
BACKGROUND: The 20-maximum trampoline jump test is a commonly used performance measure in competitive trampoline gymnastics. However, its reliability and characteristics are poorly understood. OBJECTIVE: To determine the reliability of the 20-maximum trampoline jump test and describe its characteristics. METHODS: Thirty-two national and international level trampoline gymnasts (18 ± 5 years) performed two, 20-maximal straight jump tests, separated by 24-72 hours. Time of flight (total, jumps 1-10 and jumps 11-20), force (average and peak), horizontal displacement and contact time were measured by a competition standard system. Test-retest reliability was assessed using intraclass correlation coefficient (ICC), typical error, and coefficient of variation (CV). RESULTS: Total time of flight significantly decreased between trial 1 (31.80 ± 1.98 s) and trial 2 (31.43 ± 1.99 s; p < 0.05), however test-retest reliability was excellent (ICC = 0.96, CV = 1.3%). Other time of flight and force measures significantly decreased from trial 1 to trial 2, whereas contact time increased. All secondary measures displayed very high ICC (0.95-0.99) and low CV values (0.5-1.9%), except horizontal displacement (ICC = 0.54, CV = 20.6%). CONCLUSION: The 20-maximum test possesses excellent reliability for the assessment of trampoline performance in a wide population of national and international level gymnasts.